Water and Society 2011
DOI: 10.2495/ws110081
|View full text |Cite
|
Sign up to set email alerts
|

The impact of land use change on runoff and peak flood discharges for the Nyando River in Lake Victoria drainage basin, Kenya

Abstract: The effects of land use changes on the characteristics of floods in the Nyando River basin were investigated. Historical changes in the state of land cover were derived by processing multi-temporal Landsat images. The detected changes, together with other spatial datasets were subsequently used to estimate the physically based catchment and hydrologic model parameters for runoff generation and transformation, and for channel flow routing. The results obtained indicated that the basin experienced significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Riverine runoff of an area is affected by land use changes, as was observed in Nyando river basin, Kenya, by Kundu and Olang (2011). Changes in land cover due to human activities are found to increase sedimentation in several deltas of norther Java (Lavigne and Gunnell, 2006).…”
Section: Introductionmentioning
confidence: 83%
“…Riverine runoff of an area is affected by land use changes, as was observed in Nyando river basin, Kenya, by Kundu and Olang (2011). Changes in land cover due to human activities are found to increase sedimentation in several deltas of norther Java (Lavigne and Gunnell, 2006).…”
Section: Introductionmentioning
confidence: 83%
“…Debit puncak meningkat sebesar 16% di semua 14 sub-DAS. Simulasi volume banjir di DAS juga meningkat 10% dibandingkan periode yang sama (Kundu & Olang, 2011).…”
Section: Limpasan Puncakunclassified
“…A review of several studies in East Africa by [13] found that forest cover loss increased annual discharges and surface runoff by 16 ± 5.5% and 45 ± 14%, respectively. Another study done in the Nyando River in Lake Victoria drainage basin in Kenya showed a significant increase in peak discharge in an area under deforestation located in the upstream area [14].…”
Section: Introductionmentioning
confidence: 97%